Modifikasi Algoritma Vigenere Cipher dengan Pembangkit Kunci Random Number Generator Dalam Pengamanan Citra Digital - Amalia Zebua, Shafira (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Digital image is an image that can be processed by a computer. Digital images that are not allowed to be known by others or are said to be private and are not allowed to be manipulated by other irresponsible parties. The act of manipulating, hijacking or tapping the image will cause harm to the owner of the image. The technique to reduce these actions is to use cryptographic techniques. Cryptographic techniques are very well known for securing information with a password that only the owner of the image understands. To strengthen the results of the encryption carried out by the Vigenere Cipher Algorithm, modifications are made to the Random Number Generator. The Random Number Generator used is Linear Congruent Generator which has linear recursive properties combined with modulus. So the combination of vigenere cipher with random number generator Linear Congruent Generator is very difficult for other parties to abuse the image